PENGARUH LATIHAN SAQ (SPEED, AGILITY, QUICKNESS) TERHADAP PENINGKATAN KECEPATAN DAN KELINCAHAN PADA PEMAIN SEPAK BOLA MOGEN TAHUN 2018 - Muhammad Sirajudin Mukhtar; Baiq Satrianingsih; Ismail Marzuki (Universitas Pendidikan Mandalika, 2018)
The need to practice SAQ (Speed, Agility, Quickness) in order to increase speed and agility for Mogen players when playing soccer. The purpose of this study was to determine whether or not the influence of SAQ (Speed, Agility, Quickness) exercise on speed and agility in Mogen players in 2018. The research method used by researchers was observation method, documentation method and deed test method. The study design used a pretest-posttest design (initial test and final test). The population used in this study is the overall Mogen player in 2018. The number of samples in the study conducted was 18 Mogen soccer players. The sampling technique in this study using a saturated sampling technique is a sampling technique if all members of the population can be sampled. Analysis of statistical data with a significant level of 5% for the results of the speed test obtained t-count value of -4,026 and t-table of 1,740, meaning that the t-count is greater than t-table which is -4,026> 1,740, the results are significant. Then the results of the agility t test result obtained t-count value of -9.038 and t-table of 1.740, meaning that the calculated t-value is greater than t-table which is -9.038> 1,740, the results are significant. So the conclusion is